Kepemimpinan Ayah Muntasir dalam Keberhasilan Pendidikan Pondok Pesantren Dayah Jamiah Al-Aziziyah - Abu Bakar, Miftahuddin; Abdullah, Amiruddin; Murdani, Murdani (Jurnal Seumubeuet, 2022)
Islamic boarding schools have been considered as educational institutions that have advantages. The development and success of education in Islamic boarding schools cannot be separated from the style and strategy of a leader in managing it. Muntasir's Ayah as the leader of Dayah Jamiah Al-Aziziyah has his own style and strategy in creating successful management of education in Islamic boarding schools. This study aims to determine how the style and strategy of the Ayah of Muntasir in the successful management of education in Islamic boarding schools. This research uses a qualitative approach with a single/individual case study, data collection in this study using participant observation techniques, in-depth interviews, and documentation, the research informants are mudir ma'had, namely the leader of the Dayah Jamiah Al-Aziziyah Islamic boarding school, wadir ma' had, teachers/asatidz, students and alumni. The data that has been collected is checked for validity by using a triangulation strategy. Technical data analysis is carried out by collecting data, reducing data, displaying data and drawing conclusions.The results of this research are as follows: (1) Ayah Muntasir's leadership style in the successful management of Islamic boarding school education is charismatic and democratic, (2) Ayah Muntasir's leadership strategy in the successful management of Islamic boarding school education is by: a). Improving the quality of teacher human resources, b). Improving the quality of students, c). Making the Vision, Mission and Goals of Islamic Boarding Schools the Main Target, and d), Improving Facilities and Infrastructure.